The claustrum of the ferret: afferent and efferent connections to lower and higher order visual cortical areas - Patzke, Nina; Innocenti, Giorgio M.; Manger, Paul R. (Frontiers in Systems Neuroscience, 2014)
The claustrum, a subcortical telencephalic structure, is known to be reciprocally interconnected to almost all cortical regions; however, a systematic analysis of claustrocortical connectivity with physiologicall identified lower and higher order visual cortical areas has not been undertaken. In the current study we used biotinylated dextran amine to trace the connections of the ferret claustrum with lower (occipital areas 17, 18, 19 and 21) and higher (parietal and temporal areas PPc, PPr, 20a, 20b, AEV) order visual cortical areas. No connections between the claustrum and area 17 were observed. Occipital visual areas 18, 19 and 21 revealed a reciprocal connectivity mainly to the caudal part of the claustrum. After injection into parietal areas PPc and PPr labelled neurons and terminals were found throughout almost the entire anterocaudal extent of the dorsal claustrum. Area 20b revealed reciprocal connections mainly to the caudal-ventral claustrum, although some labelled neurons and terminals were observed in the dorso-central claustrum. No projection from the claustrum to areas AEV and 20a could be observed, though projections from AEV and 20a to the claustrum were found. Only injections placed in areas PPr and AEV resulted in anterogradely labelled terminals in the contralateral claustrum. Our results suggest that lower order visual areas have clearly defined connectivity zones located in the caudal claustrum, whereas higher order visual areas, even if not sending and/or receiving projections from the entire claustrum, show a more widespread connectivity.